Conflicts of relationship between franchisor and franchisees: a study in franchises of the food branch from the point of view of the franchisee in the administrative region of Marília (SP) - Nogueira, Clariana Ribeiro; Lourenzani, Ana Elisa Bressan Smith; Dadario, Natália (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
Since franchising began in Brazil, entrepreneurs have taken a growing interest in this business format. In franchising, the franchisee owns his own business, instead of being an employee of the franchisor, and the relationship of both is governed by an agreement in which the rights and duties are predetermined. Since there is a relation of bilateral dependence between franchisor and franchisee, one must consider the best performance of the business as depending on the relationship established between them and as aiming at more efficient and coordinated management. The topic still lacks deeper, more critical studies, especially in regions too far from large centers. This study aims to analyze the franchisor—franchisee relationship, based on agency theory, as well as to map hotspots and indicate factors of conflict that lead to dissatisfaction of the parties.